Wybrane problemy badań miejsca pracy w systemie wartości - Jezior, Jagoda (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article discusses a selection issues in the sociological research on the position of work in the system of values. The examined issues are dealt with in three aspects: theoretical, methodological and empirical. The selection of issues for analysis is determined by the conceptual and methodological approach applied by Jan Szymczyk, which has to do with the fact that Szymczyk’s own analyses of the issues at hand constitute a significant part of his own research legacy. In my article, special importance is attached to Szymczyk’s views on the theory of values, his critical reflections concerning the concept of values, principles of defining values is sociology and on the methodological aspects of the related research. The research material employed is taken from selected research projects carried out in between 1996 and 2019 in the Lublin Voivodship.